Full-length transcriptome of in Medicago sativa L. roots in response to drought stress - Fang, Zhihong; Liu, Jianning; Wu, Xinming; Zhang, Yan; Jia, Huili; Shi, Yonghong (Frontiers in Genetics, 2023)
Background: Alfalfa (Medicago sativa L.), serves as a legume with high drought tolerance, is a major forage crop with a high biomass of production. However, the molecular mechanism of Alfalfa in response to drought stress are still unclear. Results: We constructed the first full-length transcriptome for Alfalfa root. 21.53Gb clean data were obtained by further data filtering, in which incorporate 566,076 reads of Insert (ROI), and 409,291 full length reads non-Chimeric (FLNC) sequences. Combined with second-generation sequencing (SGS), there were 2615, 6011, and 4617 differentially expressed genes (DEGs) in three comparisons. KEGG pathway analysis showed enrichment of ribosome, glutathione metabolism, and biosynthesis of amino acids are among the DEGs. The majority of transcription factors (TFs) from DEGs were AP2/ERF-ERF (37), C2H2 (32), and bHLH (22) bZIP (22), followed by C3H (19), MYB (18), WRKY (18), GRAS (16), and NAC (15). 32 C2H2 genes were differentially expressed in three groups. In addition, TFs annotated as C3H (19), MYB (18), GRAS (16), and NAC (15) also changed significantly in expression in the three comparisons. We found 24 genes participate in the abscisic acid (ABA) and auxin hormone signaling pathway in response to drought stress, and monitored the expression patterns of these related genes. Conclusion: The present study enhanced our understanding of the genetic diversity and complexity, and provides greater insight into the fundamental transcriptome reprogramming of Alfalfa under drought.